Burnout in nurses working in Portuguese central prisons and type of employment contract - Mendes, Aida Maria De Oliveira Cruz; Claro, Margarida; Robazzi, Maria Lúcia Do Carmo Cruz (La Medicina del Lavoro, 2014)
Background: Many studies on burnout have been conducted to try to identify the most vulnerable populations and settings for burnout. Despite the existing studies on burnout in Portuguese nurses, no studies have yet been conducted in prisons. Objectives: This study measured the levels of burnout among nurses working in prisons and their relationship to the socio-demographic variables and type of employment contract. Methods: A questionnaire on the socio-demographic and professional characteristics and the MBI-GS (Maslach Burnout Inventory – General Survey) were sent to the 124 nurses working in Portuguese central prisons, resulting in a final sample of 95 nurses. Associations between burnout levels and socio-demographic variables were identified by Pearson’s coefficient and differences between groups according to type of employment were verified using analysis of variance (ANOVA). Results: 31.57% of nurses showed both emotional and physical exhaustion and cynicism, and 6.32% lacked professional efficiency. Statistically significant differences were found (p=0.031) in terms of cynicism and the type of employment contract between nurses from the Ministry of Justice (Mean=13.55) and nurses who were individual service providers (Mean=7.25). Nurses working in prisons have higher burnout levels than nurses in general, as well as high levels of emotional and physical exhaustion (Mean=12.85) and cynicism (Mean=12.32). These findings confirm that special attention should be given to nurses working in these services.